L’effervescence pédagogique dans les collèges parisiens au xvie siècle - Véronique Castagnet-Lars (Les Cahiers de Framespa)
Considering that education and school structures were one and the same in Paris between the end of the fifteenth century and the beginning of the sixteenth century, under the eyes of the King and the University, is a major mistake. On the contrary, educational innovations caused not only the evolution of educational programs but also a change in the structure of schools. In this relatively small Parisian space, educational effervescence increased competition between colleges.